Amyloid Against Amyloid: Dimeric Amyloid Fragment Ameliorates Cognitive Impairments by Direct Clearance of Oligomers and Plaques. Issue 7 (12th January 2023) - Lee, Hee Yang; Baek, Seungyeop; Cha, Minhae; Yang, Seung‐Hoon; Cho, Illhwan; Shin, Heewon; Lee, Sejin; Kim, Hye Yun; Lee, Songmin; Shin, Jisu; Lee, Donghee; Kim, Kyeonghwan; et al.
Abstract: Amyloid‐β (Aβ) in the form of neurotoxic aggregates is regarded as the main pathological initiator and key therapeutic target of Alzheimer's disease. However, anti‐Aβ drug development has been impeded by the lack of a target needed for structure‐based drug design and low permeability of the blood–brain barrier (BBB). An attractive therapeutic strategy is the development of amyloid‐based anti‐Aβ peptidomimetics that exploit the self‐assembling nature of Aβ and penetrate the BBB. Herein, we designed a dimeric peptide drug candidate based on the N‐terminal fragment of Aβ, DAB, found to cross the BBB and solubilize Aβ oligomers and fibrils. Administration of DAB reduced amyloid burden in 5XFAD mice, and downregulated neuroinflammation and prevented memory impairment in the Y‐maze test. Peptide mapping assays and molecular docking studies were utilized to elucidate DAB‐Aβ interaction. To further understand the active regions of DAB, we assessed the dissociative activity of DAB with sequence modifications. Abstract : Based on the N‐terminal of amyloid‐β, we designed a dimeric Aβ (1–17)‐based peptide drug that crosses the blood–brain barrier and dissociates amyloid plaques and oligomers upon administration to transgenic Alzheimer model mice.